The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/c2010005
|View full text |Cite
|
Sign up to set email alerts
|

Is the Formation of Poly-CO2 Stabilized by Lewis Base Moieties in N- and S-Doped Porous Carbon?

Abstract: Abstract:The polymerization of CO 2 by Lewis basic moieties has been recently proposed to account for the high adsorption ability of N and S-doped porous carbon materials formed from the pyrolysis of sulfur or nitrogen containing polymers in the presence of KOH. Ab initio calculations performed on the ideal CO 2 tetramer complex LB-(CO 2 ) 4 (LB = NH 3 , H 2 O, H 2 S) showed no propensity for stabilization. A weak association is observed using Lewis acid species bound to oxygen (LA = H + , AlF 3 , AlH 3 , B 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To date, a common approach is to synthesize PC via the KOH activation of carbon rich precursors such as polymers and bio‐sourced materials . It has been traditional thought that the presence of nitrogen or sulfur enhanced the uptake, however, recent work has shown that this is not true, and that the oxygen (or total heteroatom content) is more important ,. In fact, the carbon content may be used as a quick guide to uptake efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a common approach is to synthesize PC via the KOH activation of carbon rich precursors such as polymers and bio‐sourced materials . It has been traditional thought that the presence of nitrogen or sulfur enhanced the uptake, however, recent work has shown that this is not true, and that the oxygen (or total heteroatom content) is more important ,. In fact, the carbon content may be used as a quick guide to uptake efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to some recent claims [17], it has been shown in multiple studies that the presence of nitrogen-or sulfur-doping in PC materials does not enhance the uptake of CO 2 or the selectivity [18][19][20]. Instead, the presence of N, S, and O are more to do with the generation of the optimum pore size and distribution [16].…”
Section: Introductionmentioning
confidence: 76%
“…All the Coulomb interaction terms in direct and exchange channels are calculated exactly to find the Born-Oppenheimer (BO) matrix elements [2] that acts as input to find the unknown SEM amplitude, following a coupled-channel methodology introduced by Calcutta Group [3]. The detailed of the theory is available in the literature [1][2][3][4][5][6][7][8][9]. Here Lippman-Schwinger type coupled integral equation in momentum space formalism [3] is used.…”
mentioning
confidence: 99%
“…The detailed of the theory is available in the literature [1][2][3][4][5][6][7][8][9]. Here Lippman-Schwinger type coupled integral equation in momentum space formalism [3] is used. The formally exact Lippman-Schwinger type coupled integral equation for the scattering amplitude in momentum space is given by [3]:…”
mentioning
confidence: 99%
See 1 more Smart Citation